A study of fungi isolated from cases of otitis media diagnosed at tertiary care hospital of Gujarat, India - Patel, Kirankumar Navnitlal; Shrimali, Gaurishanker P.; Thakor, Nilesh (International Journal of Advances in Medicine, 2016)
Background: Otitis media is commonest disease seen in children. Apart from bacteria fungus are responsible for majority of the cases of otitis media. The objective was to speculate the aetiological fungal flora which was responsible for the cases of otitis media. Methods: The present study was conducted by Department of Microbiology, B. J. Medical College, Ahmedabad during 1st May 2000 to 30th April 2002. Before conducting the study approval was obtained from institutional ethical committee for human research. Total 140 patients of otitis media were included after written informed consent. The ear discharge from each diseased middle) ear was collected and cultured on Sabouraud’s dextrose agar slant and was examined for gross and the microscopic morphology of the fungi. The organisms were identified by using a standard procedure. Data was analyzed using Microsoft exel software (Trial Version). Results: Out of 140 samples 114 (81.43%) had positive culture. out of 114 cases, 64 (56.14%) were male. Majority of the cases (32.45%) were in the age group of 0-14 years. Out of 114 positive cases, single organism was isolated in 99 (86.8%) cases. Out of total 129 strains 44 (37.9%) were gram positive, 72 (62.1%) were gram negative organisms and 13 (10.07%). Out of total 13 strains of fungus isolated 6 (46.15%) were Candida albicans and 7 (53.84%) were Aspergillus niger. Aspergillus niger is predominant isolated fungus as compared to Candida albicans. Isolation of Aspergillus niger was only seen in adults. Conclusions: Aspergillus niger and Candida albicans were found to be the common fungal causes of otitis media in our study.